Bright and biocompatible AIE polymeric nanoparticles prepared from miniemulsion for fluorescence cell imaging. Issue 35 (22nd August 2016) - Cao, Zhihai; Liang, Xiaoqin; Chen, Hangnan; Gao, Meng; Zhao, Zujin; Chen, Xiaolong; Xu, Chang; Qu, Gan; Qi, Dongming; Tang, Ben Zhong
Abstract : AIE polymeric nanoparticles with bright fluorescence, high quantum yield, low cytotoxicity, and efficient cellular uptake were prepared by miniemulsion polymerization. Abstract : Aggregation-induced emission (AIE) polymeric nanoparticles (NPs) with a size of several tens of nanometers were successfully prepared by miniemulsion copolymerization of methyl methacrylate (MMA) with an AIE monomer, 1-allyl-1-methyl-2, 3, 4, 5-tetraphenylsilole (AMTPS). The prepared AIE poly(MMA- co -AMTPS) NPs exhibited strong photoluminescence with high quantum yields. Promisingly, the brightness of AIE poly(MMA- co -AMTPS) NPs, which increased linearly with an increase in AMTPS content, could be accurately modulated via the AMTPS content in the range of 0–20 wt%. In vitro cell experiments indicated that the AIE poly(MMA- co -AMTPS) NPs were promising cell staining reagents with good biocompatibility and high photostability.